Anaphylaxis and Coronavirus Disease 2019 vaccine: a danger relationship?. Issue 5 (30th October 2021) - Tanno, Luciana Kase; Castells, Mariana; Caminati, Marco; Senna, Gianenrico; Demoly, Pascal
Abstract : Purpose of review: Anaphylactic reactions reported after Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) RNA vaccines were expected to be more frequent in atopic subjects and attributed to its polyethylene glycol component. Recent findings: Anaphylaxis to SARS-CoV2 RNA vaccines is no more frequent than in any vaccine and direct proofs for the role of its polyethylene glycol component are lacking. Summary: Vaccines against coronavirus disease 2019 (COVID-19) are an essential global intervention to control the current pandemic situation. Anaphylactic reactions have rapidly been reported after SARS-CoV2 RNA vaccines. This risk is now measured at 2.5–11/1 000 000 in the context of vaccine safety surveillance programs and only one case was documented to be due to polyethylene glycol. Suggestions for its role are indirect. The COVID-19 vaccination is rolling out vastly and surveillance programs are key to monitor severe adverse reactions, such as anaphylaxis. Anaphylaxis due to vaccine is extremely rare and specific cases should receive individualized investigation and care, highlighting the key role of allergists in the vaccination programmes.